Investigation of the removal of Ni(II) from aqueous solution using pomelo fruit peel - Van Phuc Dinh (Vietnam Journal of Science, Technology and Engineering, 2021)
The growth of numerous industries has helped many developing nations’ economies significantly in recent years. However, the governments of these nations face serious environmental issues, particularly those involving the pol-luting of industrial zones’ effluent with heavy hazardous metals. Pomelo fruit peel, an organic waste, was utilised as a biosorbent to remove Ni(II) from aqueous solutions. Some major factors influencing Ni(II) uptake such as pH, adsorption time, and initial Ni(II) concentration were examined. Several isotherm and kinetic models including the Langmuir, Freundlich, Sips, pseudo-first-order, pseudo-second- order, and intra-diffusion models were fit to the experimental data. The Ni(II) adsorption onto pomelo fruit peel was investigated. Kinetic studies showed that the Ni(II) uptake was controlled by various mechanisms. Results showed that the Ni(II) uptake obtained an equilibrium at pH=6 after 80 min at 303 K. The Sips isotherm model described the Ni(II) adsorption better than other models and the monoadsorption capacity calculated from the Langmuir model was 9.67 mg/g. The adsorption of Ni(II) fol-lowed pseudo-second-order kinetic models with three stages.